Blydskap: ’n Antwoord op beproewings volgens Jakobus 1:2-4 - Le Bruyns, C (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
Joy: an answer to trials according to James 1:2-4 In James 1:2 it is said: “Be glad when all trials fall upon you”. At first glance this phrase seems to be a contradiction in terms. How can one be glad when you fall under trials? One should rather be petrified. It is difficult to understand this instruction. This was the case even more for believers in the time of James. They were subdued not only to certain types of unfair practices but also to trials in general. It is argued that on grounds of semantic- and further textual considerations, the understanding of this phrase should be read against the background of a metallurgical metaphor. When ore is crushed and exposed to extensive heat, a precious metal is subsequently produced. In the same manner a person’s character is developed by trials. Therefore, according to James, trials should be welcomed as it is a chance to facilitate character development. The mere fact that character development has taken place should bring existential joy to a person.